Stability of a floating water droplet on an oil surface - Phan, Chi M (Langmuir : the ACS journal of surfaces and colloids, 2014)
This article presents a new configuration of a water droplet floating on oil surface. The configuration is characterized by an acute contact angle (i.e., θ2 < π/2). In contrast, the previously identified droplet had an obtuse contact angle, which was easily sunk by a small disturbance. By employing a common surfactant, the new configuration was experimentally verified in a mineral oil with a density similar to that of crude oils. The new droplet is kinetically more stable than the previous configuration and can sustain strong disturbances. The results also highlight the significance of dynamic interfacial adsorption on the stability of the floating droplet